The Right to Education for Brides in Early Marriage from the Perspective of Islamic Family Law in Kuningan - Ratu Salma Salsabila; Ahmad Rofii (UIN Siber Syekh Nurjati Cirebon, 2026)
Early marriage continues to be a social phenomenon that significantly affects the educational rights of women, particularly in Kuningan Regency. From an Islamic family law perspective, the objective of this investigation is to examine the extent to which brides' rights to education are upheld in the context of early marriage. The research examines early brides, officials of the Office of Religious Affairs, and school officials using a sociological-juridical method (normative-empirical) and a qualitative approach. Informants were identified through purposive sampling, and data were gathered through in-depth interviews and document studies. The maqasid al- shari'ah framework, specifically the principle of hifz al-'aql, was then employed to analyze the data. According to the study's findings, the interruption of brides' education is empirically caused by early marriage, and domestic burdens, economic constraints, patriarchal culture, and inadequate institutional support influence it. This condition is in direct opposition to the principle of hifz al-'aql in Islamic family law, which positions education as the primary method of safeguarding and cultivating reason. In the context of early marriage, this research is unique in integrating local empirical analysis with an Islamic family law perspective grounded in maqasid al-syari'ah, which emphasizes education as a fundamental right of women. Keywords: Early Marriage; Right to Education; Bride; Islamic Family Law; Maqasid al-Shari'ah